PARTIAL PURIFICATION,CHARACTERIZATION AND SOME KINETIC PROPERTIES OF LOW MOLECULAR WEIGHT ACID PHOSPHATASE FROM LEAVES OF GERMINATING VIGNA RADIATA SEEDS. - A. Saeed; M. Salim; R. Naz; U. Zaman; A. L. Baloch; S. Nadir; A. Saeed (Journal of Animal and Plant Sciences, 2014)
Acid phosphatase isoenzyme (AcP-II) from leaves of germinating seeds of vigna radiata (mung beans) was partially purified by CM-Cellulose chromatoghraphy, gelfiltration on Ultrogel AcA 44 and Con A-Sepharose affinity chromatoghraphy. The specific activity of 25U/ mg of protein was obtained with recovery of 4 %. The enzyme showed a purification by a factor of 86. Gel filtration experiment and sodium dodecyl sulphate polyacrylamide gel electrophoresis indicated that the isoenzyme had a molecular weight of 29 kDa. The Km value of the isoenzyme was 0.5 mM with p-nitrophenyl phosphate as substrate. The enzyme had pH optimum of 5.5 and optimum temperature of 60oC. The enzyme was inhibited by phosphate, vanadate, fluoride and molybdate. It was also strongly inhibited by Cu++, Hg++, Zn++ and Al+++. The enzyme had very little effect of inhibition by thiol specific reagents, such as iodoacetamide, N-ethyl-maleimide etc., suggesting that no -SH groups are involved in the enzyme catalysis. Dithiothreitol and β-mercaptoethanol had small activating effect at low concentrations indicating their properties as reducing agents but at their high concentrations, the activation was replaced by inhibition, suggesting that these thiols may cause a conformational change in the enzyme at a place other than the active site. Variation of Km values with pH alteration study showed that a histidine may constitute a part of an active site. This was confirmed by inhibitory effect of high concentration of iodoacetate at pH 7.2
Keywords: Acid phosphatase isoenzyme (AcP-II) from leaves of germinating seeds of vigna radiata (mung beans) was partially purified by CM-Cellulose chromatoghraphy; gelfiltration on Ultrogel AcA 44 and Con A-Sepharose affinity chromatoghraphy. The specific activity of 25U/ mg of protein was obtained with recovery of 4 %. The enzyme showed a purification by a factor of 86. Gel filtration experiment and sodium dodecyl sulphate polyacrylamide gel electrophoresis indicated that the isoenzyme had a molecular weight of 29 kDa. The Km value of the isoenzyme was 0.5 mM with p-nitrophenyl phosphate as substrate. The enzyme had pH optimum of 5.5 and optimum temperature of 60oC. The enzyme was inhibited by phosphate; vanadate; fluoride and molybdate. It was also strongly inhibited by Cu++; Hg++; Zn++ and Al+++. The enzyme had very little effect of inhibition by thiol specific reagents; such as iodoacetamide; N-ethyl-maleimide etc.; suggesting that no -SH groups are involved in the enzyme catalysis. Dithiothreitol and β-mercaptoethanol had small activating effect at low concentrations indicating their properties as reducing agents but at their high concentrations; the activation was replaced by inhibition; suggesting that these thiols may cause a conformational change in the enzyme at a place other than the active site. Variation of Km values with pH alteration study showed that a histidine may constitute a part of an active site. This was confirmed by inhibitory effect of high concentration of iodoacetate at pH 7.2